HUBUNGAN KREATIVITAS MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA DI KELAS IV SDN 32 CAKRANEGARA TAHUN AJARAN 2021/2022 - Nurjanah Nurjanah; Darmiany Darmiany; Abdul Kadir Jaelani; Mansur Hakim (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
The purpose of this study was "To determine the relationship between teacher teaching creativity and student motivation in Class I V SDN 32 Cakranegara". This research was structured using quantitative research methods with the type of causality correlational research or one-way relationship where this research was conducted to find out the relationship between teacher teaching creativity and student learning motivation. The population in this study were elementary school students, namely fourth grade students at SD Negeri 32 Cakranegara which consisted of 2 classes, namely class A totaling 27 students and class B totaling 28 students. The total number of classes A and B is 55 students. The data collection technique or method that will be used in this research is a questionnaire (questionnaire) and the research data will be analyzed by descriptive statistical analysis and inferential statistics. Based on the results of the Pearson correlation test, it shows that there is a relationship between teacher teaching creativity and the learning motivation of fourth grade students at SDN 32 Cakranegara in the 2021/2022 academic year. Obtaining rcount > rtable or Pearson correlation of 0.413 > 0.235 With Sig. (2-tailed) of 0.000 < 0.05. Being in the strong category in the interpretation table of the correlation coefficient value of r, so it can be said that the results of this study are significant.